Perancangan Media Promosi SMP IT Dar El Iman dalam Bentuk Audio Visual - Eka Febdianda `Ramadhan (Judikatif: Jurnal Desain Komunikasi Kreatif, 2020)
SMP IT Dar El Iman is a modern school that stands in the center of the city of Padang which was founded in 2015 under the auspices of the Dar El Iman foundation, where SMP IT Dar El Iman has complete facilities and quality graduates. The absence of a promotional video, made the author to appoint Dar El Iman IT Middle School as the title of the Final Project with the title "Designing a Dar El Iman IT Middle School Promotion Video, which in the Dar El Iman IT Middle School Promotion Video will show complete facilities and student activities. which is combined with visuals and the selection of Islamic nuanced backsound. Furthermore, it is analyzed using SWOT analysis theory. This is done as a creative approach to reach the target audience area, so that the aims and objectives of the video are right on target and can increase enthusiasts from the Dar El Iman IT Middle School.